Igneous Rock Associations 13: Focusing on the Central American Subduction Zone - Walker, James; Gazel, Esteban (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2014)
Central America has recently been an important focus area for investigations into the complex processes occurring in subduction zones. Here we review some of the new findings concerning subduction input, magma production and evolution, and resultant volcanic output. In the Nicaraguan portion of the subduction zone, subduction input is unusually wet, likely caused by extensive serpentinization of the mantle portion of the incoming plate associated with bending-related faulting seaward of the Middle America trench. The atypical influx of water into the Nicaraguan section of the subduction zone ultimately leads to a regional maximum in the degree of mantle melting. In central Costa Rica, subduction input is also unusual in that it includes oceanic crust flavored by the Galapagos plume. Both of these exotic subduction inputs are recognizable in the compositions of magmas erupted along the volcanic front. In addition, Nicaraguan magmas bear a strong chemical imprint from subducting hemipelagic sediments. The high-fieldstrength- element depletions of magmas from El Salvador through Costa Rica are related to local variations in the depth to the subducting Cocos plate and, therefore, to segmentation of the volcanic front. Minor phases, probably amphibole or rutile, control these variable depletions. Silicic magmas erupted along the volcanic front exhibit the same along-arc geochemical variations as their mafic brethren. This and their mantle-like radiogenic isotopic compositions suggest the production of juvenile continental crust all along the Central American subduction zone. Punctuated times of enhanced magmatic input from the mantle may aid in crustal development.